Pengaruh Country Of Origin Dan Reputasi Merek Terhadap Loyalitas Konsumen Natasha Skin Care Di Kabupaten Dan Kota Bekasi - Novi Lestari; Fitria Nurani Zen (LPPM STIE Bisnis Internasional Indonesia, 2023)
The research focuses on The Influence of Country Of Origin and Brand Reputation on Consumer Loyalty of Natasha Skin Care in Bekasi District and City. aims to find out how the influence of country of origin on Natasha Skin Care products, how the influence of brand reputation on beauty products Natasha Skin Care., and to determine the influence of country of origin and brand reputation on beauty products Natasha Skin Care.